Pengembangan Bracket Wireline Valve menggunakan Metode QFD pada PT. ABC - Yuriko Adeputra; Bachtiar H. Simamora (JURNAL PENDIDIKAN DAN KEWIRAUSAHAAN, 2023)
The focus of the research is to find solutions based on lesson learning bulletins shared by the company in the form of case studies at PT. ABC clumsy occurs in wireline valve equipment. This study aims to improve by determining the key factors in the design of wireline valve brackets that consumers expect and can reduce work accident factors. The method used in this study is the Application of Quality Function Deployment (QFD) to design and develop QFD products in determining customer needs and technical tequirement for making House of Quality (HoQ) matrices, after that continued making part deployment matrices To help research determine priorities and ensure the characteristics of product components are connected to customer needs. The results of the study produced a prototype with a simple bracket design concept, dimensions of 240x50x423 mm, the weight of the wireline valve bracket prototype is 6 kg, installation time <60 seconds, and the wireline valve bracket has received a rust-resistant coating, namely Mn. Phospating, has also passed the 1040 kg load test and magnetic particle inspection test , for the color according to PT. ABC and wireline valve brackets can be installed on all three sides of the frame. Wireline valve brackets that have been designed are a solution to problems because they have advantages in terms of safety, design and compliance with specifications.